Allocation of general budget resources in light of the economic intellectual orientation in Iraq after 2003 (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research seeks to clarify the allocation of general budget resources in Iraq in light of Iraq's abandonment of the socialist economic intellectual orientation based on central planning and the shift towards a market economy after the change that occurred in the political system in 2003. What are the most important reasons for the shift, the procedures and strategy adopted for the shift, and its impact on the Iraqi economy and the extent of its contribution to diversifying the resources of the general budget or maintaining reliance on the oil resource as the sole source of obtaining resources and how to distribute those resources to the economic and social sectors. The research reached the conclusion that there is ambiguity in the economic intellectual orientation in Iraq and it had a role in influencing the allocation of general budget resources and distributing them to the economic sectors.